Environmental pollution & toxicology - Joshi, B. D.; Joshi, P. C.; Joshi, Namita (New Delhi : A.P.H. Pub. Corp., 2008)
Contributed seminar articles organized by Indian Academy of Environmental Sciences, Hardwar.
Keywords: Pollution -- Environmental aspects; Environmental toxicology